Sputtering and redeposition of ion irradiated Au nanoparticle arrays: direct comparison of simulations to experiments - Henry Holland-Moritz; Andrey Ilinov; Flyura Djurabekova; Kai Nordlund; Carsten Ronning (New Journal of Physics, 2017)
Ion beam processing of surfaces is well known to lead to sputtering, which conventionally is associated only with erosion of atoms from the material. We show here, by combination of experiments and a newly developed Monte Carlo algorithm, that in the case of nanoparticles in a regular two-dimensional array on surfaces, the redeposition of sputtered atoms may play a significant role on the system development. The simulations are directly compared to in situ experiments obtained using a dual focused Ga ^+ ion beam system and high resolution scanning electron microscopy, and explain the size evolution by a combination of sputtering and redeposition of sputtered material on neighboring particles. The effect is found to be dependent on the size of the nanoparticles: if the nanoparticle size is comparable to the ion range, the reposition is negligible. For larger nanoparticles the redeposition becomes significant and is able to compensate up to 20% of the sputtered material, effectively reducing the process of sputtering. The redeposition may even lead to significant growth: this was seen for the nanoparticles with the sizes much smaller than the ion range. Furthermore, the algorithm shows that significant redeposition is possible when the large size neighboring nanoparticles are present.